Biliary Microbiota in Choledocholithiasis and Correlation With Duodenal Microbiota - Han, Jinyan; Wu, Shuodong; Fan, Ying; Tian, Yu; Kong, Jing (Frontiers in Cellular and Infection Microbiology, 2021)
Background: The pathogenesis of choledocholithiasis is closely related to the role of bacteria. However, little is known about the predictive role of bile bacteria in clinical conditions of patients and the compositional and functional characteristics of biliary microbiota in choledocholithiasis. Methods: To investigate the predictive value of biliary bacteria, clinical data of 488 patients with choledocholithiasis were collected. The predictive value of common bile bacteria to patients’ clinical conditions was analyzed by logistic regression. Samples of bile and corresponding duodenal juice from 10 selected patients with choledocholithiasis were obtained, and the composition and function of microbial communities were analyzed based on 16S rRNA sequencing and Tax4Fun. Results: The clinical conditions of patients with choledocholithiasis, such as recurrence, the severity of acute cholangitis, and duration of hospital stay were closely related to different species of bile bacteria as well as antimicrobial-resistant bacteria. Employing 16S rRNA sequencing, the dominant phyla of biliary and duodenal microbiota were Proteobacteria and Firmicutes. The top three core microbiota at the genus level were Escherichia–Shigella, Fusobacterium, and Enterococcus. Escherichia coli accounted for the most abundant annotated species in both. Differences in composition between biliary and duodenal microbiota were not significant according to the alpha and beta diversities. Differential abundant features were not found in biliary microbiota indicated by A linear discriminant analysis effective size algorithm. The major pathways identified in biliary and duodenal microbiota were related to membrane transport, translation, replication and repair, carbohydrate and amino acid metabolism. However, no significant difference in those major pathways, as well as antimicrobial-resistance patterns, was observed between biliary and duodenal microbiota. Conclusion: Our study first demonstrates the predictive contribution of biliary bacteria to the clinical conditions of patients with choledocholithiasis, and then it offers new insights into the compositional and functional features of biliary and duodenal microbiota. Similarities between biliary and duodenal microbiota support the theory of bacterial duodenal–biliary reflux in patients with choledocholithiasis. Meanwhile, when it is impracticable to obtain a bile sample, duodenal juice may be used as an alternative for bacterial culture and susceptibility tests.